The numerical solution of the telegraph equation by the Alternating Group Explicit (AGE) method - Evans, DJ; Bulut, H (Taylor & Francis Ltd, 2003)
In this paper, the Alternating Group Explicit (AGE) method is developed from a judicious splitting of the implicit equations derived from the finite difference discretisation of the partial differential equations. The resulting equations can be reformulated in a (2 x 2) explicit form resulting in a new stable and efficient method. Finally, the AGE method is used to investigate the numerical solution of the Telegraph equation in various 2D forms.
Keywords: the AGE method; telegraph equation